The Effect of Learning Videos on Students' Learning Comprehension Level - Rizky Adzan Maulana; Rina Maryanti (Universitas Pendidikan Indonesia (UPI), 2020)
The Covid-19 pandemic that has hit since 2019 and is currently one of the effects that is felt by students, especially in Indonesia. Since the pandemic, the education system that used to be face-to-face has now shifted to online. The purpose of this study was to determine the effect of learning videos on the level of students' understanding of learning. This study uses a mix method consisting of qualitative and quantitative analysis techniques, namely descriptive analysis. The results showed that students preferred learning that was carried out using interesting learning videos and also students understood more through learning videos. Due to the use of zoom or other media, the majority are constrained by the absence of internet quota. WhatsApp groups are a fairly easy alternative and all teachers can use the WhatsApp group facility. Learning videos are proven to be able to increase students' understanding in learning.